THE SYSTEM OF PART-TIME JOB SALARY UNDER ISLAMIC ECONOMIC LAW AND THE GOVERNMENT REGULATION: A case study at Maroon Café Banda Aceh, Indonesia - Aisyatul Humaira; Bukhari Ali (JURISTA: Jurnal Hukum dan Keadilan, 2025)
The growth of part-time work systems in the culinary business sector, particularly among micro and small enterprises, has created new challenges in human resource management, especially concerning workload fairness and wage systems. Café Maroon in Banda Aceh is one such business that applies a part-time work scheme for its employees. This study aims to analyze the system of workload determination and the relevance of part-time employee wages at Café Maroon based on the perspective of the Ijarah ‘Ala al-‘Amal contract in fiqh muamalah (Islamic commercial jurisprudence) and Government Regulation (PP) No. 36 of 2021 concerning Wages. This research employs a descriptive qualitative method with a normative and empirical juridical approach. Data were collected through in-depth interviews, direct observation, and documentation involving part-time employees and the management of Café Maroon. The results indicate that the part-time work system at Café Maroon has fulfilled aspects of work agreement and wage payment timing. However, an imbalance remains between the workload and the wages provided. From the perspective of Ijarah ‘Ala al-‘Amal, clarity of work and fairness in compensation have not been fully implemented. Similarly, within the framework of Government Regulation No. 36 of 2021, wage determination has not yet reflected the principle of a decent living as mandated by the regulation. This study recommends the need for fair and proportional adjustments to part-time wage policies, as well as the formulation of written employment contracts as a form of legal protection that aligns with both fiqh muamalah principles and positive law.